Low temperature deposition of hydrogenated nanocrystalline SiC films by helicon wave plasma enhanced chemical vapor deposition - 496878 Yu, Wei; Lu, Wanbing; Teng, Xiaoyun; Ding, Wenge; Han, Li; Fu, Guangsheng
PSZJBL